Palm silage forage with the cassava and sugarcane bagasse by-products: Review - Dos Santos, Maria; Cunha dos Santos, Betina Raquel (Pubvet, 2018)
One of the great challenges of animal production in Brazil is to find food alternatives available according to regional characteristics, efficient, low cost, meet the needs of animals and are environmentally correct. In this sense, it is important to evaluate the quality of cultural residues and agroindustrial residues that have potential for use in ruminant feeding, and that can also be made available in the period of food shortages, where animal supplementation is necessary for systems viability productive. The objective of this review is to compile information to formulate a silage based on forage palm intercropped with the cassava and sugarcane bagasse residues, which are high in nutritional value and do not cause digestive problems for animals. PH, dry matter (DM), mineral matter (MM), crude protein (CP), ethereal extract (EE), neutral detergent fiber (NDF), acid detergent fiber (FDA), silage sensory analysis and of gaseous losses. From the present study, we intend to generate and make available information and alternatives regarding forages kept in the form of silage and, consequently, to contribute to the increase of the profitability of several segments of the productive chain of grazing cattle and sheep.